Efektivitas Iklan dalam Menumbuhkan Brand Awareness SMA Sampoerna - Fahrizal Sukma; Ma'mun Sarma; Muhammad Syamsun (Institut Pertanian Bogor, 2015)
To compete with other schools, Sampoerna High School has been implementing advertisement programs in printed and electronic media. Moreover, advertisement programs that have been implementing are to increase brand awareness in public. The main aim of this research is to analyze factors that influencing. Previous researches and literatures review show that advertisement’s effectiveness is effected by the endorser's quality, the appropriate selecting of advertisement media and the attractiveness of advertisement’s message. Then the advertisement’s effectiveness enhances the brand awareness. The respondents are the parents of Sampoerna High School’s students who live in Jakarta, Bogor, Tangerang, and Bekasi (Jabotabek). The data collected by a cencus to 80 parents on July to October 2014. The data that collected has processed using Structural Equation Model (SEM). The result of SEM analysis indicates that the attractiveness of advertisement’s message has significant effect to effectiveness of advertisement, and advertisement’s effectiveness shows significant effect to brand awareness’ enhancement. Moreover, the appropriate selecting of advertisement media also shows significant effect to brand awareness. Based on the results, in order to have an effective advertisement in gaining brand awareness of Sampoerna High School, the approach of the advertisement campaign should be focusing on enhancement of the attractiveness advertisement’s message